2009
DOI: 10.1538/expanim.58.497
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Helicobacter hepaticus, Murine Norovirus, and Pneumocystis carinii and Eradication Efficacy of Cross-Fostering in Genetically Engineered Mice

Abstract: Abstract:We investigated the prevalence of Helicobacter hepaticus, murine norovirus (MNV), and Pneumocystis carinii and the efficacy of cross-fostering for their eradication in 49 genetically engineered mouse (GEM) strains at our institute. Prevalences of H. hepaticus, MNV, and P. carinii were 33.9, 36.5, and 8.6%, respectively, and immunodeficient strains showed relatively higher prevalence of the 3 pathogens than immunocompetent strains. Additionally, the same immune phenotype strains showed similar prevalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 24 publications
0
13
1
Order By: Relevance
“…The animals were housed in groups (sex-matched, 2-5 animals) in a room with a 12 h light/12 h dark cycle under specific pathogen-free conditions (see supplement Table 1 online at http://lan.sagepub.com) [AQ1] in IVCs (Greenline GM500; Tecniplast, Hohenpeißenberg, Germany) with 60 air changes per hour and a positive pressure mode (15)(16)(17)(18)(19)(20)(21)(22). The mice were kept on wood fiber bedding (Lignocel 3/4-S; JRS, Rosenberg, Germany) with weekly cage changes, and received sterile-filtered water along with a standard rodent diet (Altromin 1314; Altromin Spezialfutter, Lage, Germany) ad libitum.…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…The animals were housed in groups (sex-matched, 2-5 animals) in a room with a 12 h light/12 h dark cycle under specific pathogen-free conditions (see supplement Table 1 online at http://lan.sagepub.com) [AQ1] in IVCs (Greenline GM500; Tecniplast, Hohenpeißenberg, Germany) with 60 air changes per hour and a positive pressure mode (15)(16)(17)(18)(19)(20)(21)(22). The mice were kept on wood fiber bedding (Lignocel 3/4-S; JRS, Rosenberg, Germany) with weekly cage changes, and received sterile-filtered water along with a standard rodent diet (Altromin 1314; Altromin Spezialfutter, Lage, Germany) ad libitum.…”
Section: Animalsmentioning
confidence: 99%
“…[13][14][15][16] In the present study, exhaust air prefilter quantitative reverse transcription PCR (RT-qPCR) was compared with serological monitoring of soiled bedding sentinels for the detection of murine norovirus (MNV) in a proof of principle field study with unknown prevalence, and also in an IVC rack with known MNV prevalence in order to determine detection limits. MNV was chosen because of its high prevalence worldwide [17][18][19][20][21] and as the most commonly detected viral agent in laboratory mice. 6 Since MNV infections do not cause clinical signs in immunocompetent or even most immunodeficient mice, new infections may remain undetected even when highly prevalent, and soiled bedding sentinels cannot be reliably used to detect infections.…”
mentioning
confidence: 99%
“…Murine norovirus (MNV) is the most common pathogen in biomedical research mice worldwide [4] with a reported prevalence as high as 64% [5-10]. Following the discovery of MNV-1 in immunocompromised mice [2], additional MNV strains have been isolated from laboratory mice that form one serogroup, despite differences in biological phenotypes [11].…”
Section: Introductionmentioning
confidence: 99%
“…DNA to be present in 16.1% of fecal pellets from mice and 6.6% from rats [19]. Another study performed in genetically engineered mice reported a 33.9% PCR prevalence of H. hepaticus in the cecum of 236 mice representing 46 strains [20]. The authors concluded that cross‐fostering as a rederivation method for H. hepaticus eradication, was probably not appropriate [20].…”
Section: Gastric and Enterohepatic Non‐h Pylori Helicobacter Speciesmentioning
confidence: 99%